Shape Memory Polyurethane Based On Palm Oil Polyol - Rashid, Tuan Nur Izzah Tuan Ab (Universiti Sains Malaysia, 2015)
In this study, shape memory polyurethane (SMPU) was prepared based on palm oil polyol (POP) to reduce the usage of petrochemical based polyol. The amount of POP used was up to 20% and the total reaction time for prepolymer preparation was 2.5 to 5 hours. POP based SMPU was prepared via two-step polymerization process. The effect of POP addition and reaction time of POP were investigated using thermal analysis, mechanical and shape memory properties. The crystallinity of SMPU decreased with addition of POP due to the formation of hard segments that restrict the crystallization of PCL crystals. However, the presence of crystalline structure was still sufficient to exhibit excellent shape fixity up to 20% molar ratio of POP content. Even though the shape recovery does not achieved 100% recovery, it can be classified as a good recovery because it was recovered almost to 100%. It was also found that the mechanical properties were changed with addition of more POP content and that the maximum values were obtained at 10% molar ratio POP based SMPU. The mechanical properties based on reaction time also showed maximum value at 4.5 hours for both 10% and 20% molar ratio of POP. Meanwhile, the reaction time at 4.5 hours showed minimum value of crystallinity for both molar ratios. Based on this study, the SMPU based on 10% POP showed improved thermal, mechanical and shape memory properties compared to pure SMPU. The reaction time at 4.5 hours also showed an excellent result toward the thermal, mechanical and shape memory properties.